👤

{3×[12+(6+2×a+3×b)÷5] -9}÷6+15 = 21

Răspuns :

{ 3 * [ 12 + ( 6 + 2 * a + 3*b ) : 5 ] - 9 } : 6 +15=21
{ 3 * [ 12 + ( 6 + 2a +3b ) : 5 ] -9 } : 6 = 21 - 15
{ 3 * [ 12 + ( 6 + 2a +3b ) : 5 ] - 9 } : 6 = 6
3 * [ 12 + ( 6 + 2a + 3b ) : 5 ] - 9 = 6 * 6
3 * [ 12 + ( 6 + 2a +3b ) : 5 ] - 9 = 36
3 * [ 12 + ( 6 + 2a + 3b ) : 5 ] = 36 + 9
3 * [ 12 + ( 6 + 2a + 3b ) : 5 ] = 45
12 + ( 6 + 2a + 3b ) : 5 = 45 : 3
12 + ( 6 +2a +3b ) : 5 = 15
12 + ( 6 + 2a + 3b ) = 15 * 5
12+ ( 6 +2a +3b ) = 75
6 + 2a +3b = 75 - 12
6 + 2a +3b = 63
2a + 3b = 63 - 6
2a + 3b = 57
 
de aici nu mai stiu

{3×[12+(6+2×a+3×b)÷5] -9}÷6+15 = 21
{3
×[12+(6+2×a+3×b)÷5]-9}÷6=21-15
                                                   =6
3×[12+(6+2×a+3×b)÷5]-9=6×6
                                          =36
3×[12+(6+2×a+3×b)÷5]=36+9
                                        =45
12+(6+2×a+3×b)÷5=45÷3
                                  =15
 12+(6+2×a+3×b)=15×5
                               =75
 6+2×a+3×b=75-12
                      =63
2×a+3×b=63-6
                =57
De aici cred ca poti face singur/a.